Anthraquinones and Other Constituents from the Stem Bark of Cassia nodosa - Jain, Renuka; Rawat, Sapna; C. Jain, Satish (Asian Journal of Chemistry, 2011)
Thirteen compounds including four anthraquinones were isolated from the stem bark of Cassia nodosa. Their structures were elucidated as palmitic acid, lupenone, lupeol, β-sitosterol, stigmasterol, β-sitosterol-β-D-glucoside, eicosanoic acid, ethyl cerotate, chrysophanol, physcion, 1,5-dihydroxy-3-methoxyanthraquinone, 1,5-dihydroxy-3-methoxy-7-methylanthraquinone and pinitol. All of these, except chrysophanol have been isolated for the first time from the stem bark of this plant.